Analysis of Determinants Affecting the Distribution of MSME Funds in Indonesia: A Study of the VECM Approach - Ashary, M. Habib; Irsyadillah, Muhammad Ridha; Laila, Nisful (Islamic Economics Journal, 2025)
This study analyzes the dynamic relationship between Islamic monetary instruments (SBIS, PUAS, and the PLS mechanism) and the distribution of MSME financing in Indonesia, using a Vector Error Correction Model (VECM) for the period January 2014 to December 2023. The estimation results indicate significant policy transmission challenges: SBIS has a negative and significant effect on MSME financing. This crucial finding indicates that SBIS functions as a “liquidity trap,” encouraging Islamic banks to place funds in low-risk liquid instruments rather than in risky real-sector financing, such as MSMEs. Meanwhile, PUAS and the underlying PLS mechanism are statistically insignificant, indicating risk aversion and operational barriers to profit-sharing contracts. IRF and FEVD analyses reinforce the conclusion that policy transmission remains weak, with MSME financing variations dominated by internal bank shocks. Theoretically, this study reveals a critical gap in the Mudarabah-based monetary framework, where liquidity instruments sacrifice the goal of promoting the real economy. The practical implications require regulators to redesign liquidity instruments (such as SBIS) to better encourage real-sector incentives, thereby strengthening the alignment between sharia principles and national economic development.